(Invited) GaN Homoepitaxial Growth and Substrate-Dependent Effects for Vertical Power Devices. (8th September 2020) - Hite, Jennifer K.; Mastro, Michael A; Anderson, Travis J.; Gallagher, James C.; Ebrish, Mona; Freitas, Jaime A.
Abstract : Raman and photoluminescence mapping are used to sort GaN native substrates into two categories: those with uniform free carrier concentration and those with large variations in carrier concentration. Further characterization after growing 2-5 µm of homoepitaxial GaN by metal organic chemical vapor deposition shows the variations in the substrate carry into the epitaxial films, as observed with both mapping techniques. This is also supported by low temperature photoluminescence measurements, which show a broadening of the near band edge peak in epitaxy on the inhomogeneous substrates.